Humanitarian crises and migration causes, consequences and responses - Martin, Susan Forbes; Weerasinghe, Sanjula S.; Taylor, Abbie 1988- (Routledge, 2014)
This timely book brings together leading experts from multi-disciplinary backgrounds to reflect on diverse humanitarian crises and to shed light on a series of exploratory questions: In what ways do people move in the face of crisis situations? Why do some people move, while others do not? Where do people move? When do people move, and for how long? What are the challenges and opportunities in providing protection to crisis migrants? How might we formulate appropriate responses and sustainable solutions, and upon what factors should these depend? This book is divided into four parts, with an introductory section outlining the parameters of 'crisis migration', conceptualizing the term and evaluating its utility. This section also explores the legal, policy and institutional architecture upon which current responses are based. Section Two presents a diverse set of case studies, from the earthquake in Haiti and the widespread violence in Mexico, to the on-going exodus from Somalia and environmental degradation in Alaska and the Carteret Islands, among others. Section Three focuses on populations that may be at particular risk, including non-citizens, migrants at sea, those displaced to urban areas, and trapped populations. The concluding section maps the global governance of crisis migration and highlights gaps in current provisions for crisis-related movement across multiple levels